Answer:
1
Step-by-step explanation:
move up one and over one, 1/1 = 1
Answer:
The answere is (9,3)
Step-by-step explanation:
first equation
x - 2y = 3
9 - 2(3) = 3
9-6 = 3
3 = 3
second equations
2x - 3y = 9
2(9) - 3(3) = 9
18 - 9 =9
9 = 9
or
x - 2y = 3
x = 2y + 3
2(2y + 3 ) - 3y = 9
4y +6 - 3y = 9
y + 6 = 9
y =3
x - 2(3) = 3
x - 6 =3
x = 9
so (9,3)
i hope this helpful
Answer:
2/9
Step-by-step explanation:
Hope this helps! <3
Answer:
A= 9 , B= 4 , C= 18
Step-by-step explanation:
if u need a in depth explanation text me in the comments :)
Answer: Third Choice. x= 6 1/3
Step-by-step explanation:
Given
f(x) = 9x² - 54x - 19
Completing the square
3x -19
3x 1
Substitute back to the function
f(x) = (3x-19) (3x+1)
Simplify
x= 6 1/3 or -1/3
Hope this helps!! :)
Please let me know if you have any questions